2019
DOI: 10.5114/amsad.2019.84447
|View full text |Cite
|
Sign up to set email alerts
|

PON1 concentration and high-density lipoprotein characteristics as cardiovascular biomarkers

Abstract: Introduction: Serum paraoxonase 1 (PON1) is now known to be related to cardiovascular diseases (CVD). The aim of this study was to determine the relationship between PON1 concentration and high-density lipoprotein (HDL) subclasses in patients with proven CVD, cardiovascular risk factors but no CVD (CRF), and in healthy controls (control group). Material and methods: A case-control study was carried out with 69 volunteers from the Mexican Institute of Social Security, Mexico. Clinical parameters, lipid profile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
1
6
1
1
Order By: Relevance
“…We observed differences in the activities of PON1 according to Q192R genotype. The genotype distribution found in the current study was not different from that found in other Mexican populations [10,[53][54][55]. Few studies have reported PON1 specific activities.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…We observed differences in the activities of PON1 according to Q192R genotype. The genotype distribution found in the current study was not different from that found in other Mexican populations [10,[53][54][55]. Few studies have reported PON1 specific activities.…”
Section: Discussioncontrasting
confidence: 70%
“…In this regard Mota et al [56] reported specific PON1 AREase (0.15 ± 0.06 U/ng) and PONase (0.56 ± 0.23 U/µg) activities in an Iranian population; and found a lower concentration of PON1, but higher AREase and PONase activities than the present study. González et al [55] reported that specific PON1 LACase activity is not influenced by PON1 polymorphism genetics. These results are in agreement with those found in this study, in which we did not observe in the LACase activity among the Q192R genotypes either before or after red wine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of PON1 [33] and APEH in the list of implicated genes emphasizes the diverse molecular mechanisms underlying CAD development. These findings underscore the complex interplay of lipid metabolism, peptide metabolism, and plaque formation in the pathophysiology of CAD.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed its ability to hydrolyse homocystein thiolactone, a risk factor for cardiovascular diseases (Zafiropoulos et al, 2010). Cardio protective characteristic of PON1 is supported by several studies conducted in vitro (Mackness et al, 1991, González et al, 2019Grzegorzewska et al, 2021) and in vivo (Shih et al, 1998).…”
Section: Introductionmentioning
confidence: 96%
“…PON1 activity is found to be reduced in many disease conditions such as cardiovascular diseases (González et al, 2019;Murillo-González et al, 2020;Grzegorzewska et al, 2021), thyroid disorders (Azizi et al, 2003), cancers (El-Lebedy et al 2014), diabetes mellitus (Savu et al, 2014), chronic renal failure (Prakash et al, 2010), chronic liver damage (Ferre et al, 2002) and psychiatric disorders (Moreira et al, 2019). The comparison of PON1 activity and/ polymorphism between healthy individuals and patients require baseline data of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%